Robust Variable Structure Controllers for Axial Active Magnetic Bearing - Sinan BAŞARAN; Selim SIVRIOĞLU (International Journal of Applied Methods in Electronics and Computers, 2016)
This work focuses on robust variable structure control of a rotor-axial active magnetic bearing system. The electromagnetic force generated by active magnetic bearing is highly nonlinear characteristics. On the other hand, the magnetic force coefficient is a calculated value and its real value is not truly identified, therefore, robustness is a great importance in the operation of the active magnetic bearings system. On this works Lyapunov based three different type of variable structure controllers are proposed and experimentally tested. Robustness of the controllers were tested experimentally by creating some parametric uncertainty in the control system using an external disk mass attached to the rotor. The results of the controllers are also compared with conventional and linear robust controllers.